Controller design for PMSG-wind turbines - Wu, Haiqiang (2014)
Wind energy, as one of the clean and renewable energy resources, is a possible alternative to solve urgent problems such as fossil fuel depletion, energy demand growth, environmental pollution and so on. However, the intermittent and seasonal characteristics of wind make it difficult to utilize this natural gift efficiently.